On the characteristics of multistage evacuated solar distillation - Ahmed, Mirghani Ishak; Hrairi, Meftah; Ismail, Ahmad Faris (Elsevier, 2009)
This paper proposes a new multistage evacuated solar distillation system that was designed to increase the productivity and improve the efficiency of the simple solar still. The solar still works by virtue of the higher evaporation rate under vacuum conditions. A mathematical model for the system was developed and used to optimize the system design. Fluent software was used to simulate the simultaneous heat–mass processes of the still. NASTRAN software was used for the structural analysis. The system components were fabricated and the overall system was assembled. The preliminary results showed a significant improvement of the overall productivity. Indeed, the total productivity of the solar still is affected very much by changing the internal pressure. The productivity decreased as the pressure increased due to the lower evaporation rates at the higher pressure values. The influence of the characteristic height variation on the still's estimated productivity was found to be very strong. As the height increases the productivity decreases significantly.